2013
DOI: 10.1016/j.physleta.2013.07.021
|View full text |Cite
|
Sign up to set email alerts
|

κ-Poincaré–Hopf algebra and Hopf algebroid structure of phase space from twist

Abstract: We unify κ-Poincaré algebra and κ-Minkowski spacetime by embedding them into quantum phase space.The quantum phase space has Hopf algebroid structure to which we apply the twist in order to get κ-deformed Hopf algebroid structure and κ-deformed Heisenberg algebra. We explicitly construct κ-Poincaré-Hopf algebra and κ-Minkowski spacetime from twist. It is outlined how this construction can be extended to κ-deformed super algebra including exterior derivative and forms. Our results are relevant for constructing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 86 publications
1
44
0
Order By: Relevance
“…In [40], a phenomenological analysis related to vector-like deformations of the relativistic quantum phase space and relativistic kinematics was elaborated up to first order in the deformation, particularly on particle propagation in spacetime. Note that if NC coordinatesx μ close a Lie algebra inx μ , then the corresponding deformed quantum phase space has a Hopf algebroid structure [46][47][48][49]. Otherwise, the coproduct is non-coassociative and the corresponding structure should be quasi-bialgebroid.…”
Section: Outlook and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [40], a phenomenological analysis related to vector-like deformations of the relativistic quantum phase space and relativistic kinematics was elaborated up to first order in the deformation, particularly on particle propagation in spacetime. Note that if NC coordinatesx μ close a Lie algebra inx μ , then the corresponding deformed quantum phase space has a Hopf algebroid structure [46][47][48][49]. Otherwise, the coproduct is non-coassociative and the corresponding structure should be quasi-bialgebroid.…”
Section: Outlook and Discussionmentioning
confidence: 99%
“…If the star product is associative, the twist operator Eq. (18) satisfies the cocycle condition in the Hopf algebroid sense and vice versa [47][48][49][50][51][52].…”
Section: Star Product and Twist Operatormentioning
confidence: 99%
“…The corresponding twist does not satisfy the cocycle condition in the Hopf algebra sense, but it does in the Hopf algebroid sense [31,35,36,37].Generally, for noncommutative coordinates (7), the corresponding twist in the Hopf algebroid approach is given by [23,38]…”
Section: κ-Deformed Relativistic Quantum Phase Spacementioning
confidence: 99%
“…As in the previous subsection, it is easily shown that using the relations between the two realizations and the homomorphism property of the coproduct, one obtains the same expressions. However, a crucial point in showing this for the coproduct of M N µν are the so-called tensor identities [31,35,36,37]. They can be calculated from the undeformed ones, R 0 = x µ ⊗ 1 − 1 ⊗ x µ = 0, using the twist operator.…”
Section: Relation Between Natural and Left Covariant Realizationsmentioning
confidence: 99%
See 1 more Smart Citation